Power and principle: the politics of international criminal courts - Rudolph, Christopher (Cornell University Press, 2017)
Introduction : the light of justice -- Power and principle from Nuremberg to The Hague -- Nested interests and the institutional design of the International Criminal Court -- Explaining the outliers : domestic politics and national interests -- Power, principle, and pragmatism in prosecutorial strategy -- Conclusion : between power and principle